2014
DOI: 10.1088/0953-4075/47/10/105001
|View full text |Cite
|
Sign up to set email alerts
|

Analytical theory of charge-exchange-caused dips in spectral lines of He-like ions from laser-produced plasmas

Abstract: Previously we discovered a way for producing not-yet-available fundamental data on charge exchange between multicharged ions, virtually inaccessible by other experimental methods. It was based on the formation of dips (called x-dips) in spectral lines of hydrogen-like ions from laser-produced plasmas. At that time the x-dip phenomenon was considered to be possible only in spectral lines of hydrogenic systems: due to the existence of exact algebraic (higher than geometrical) symmetries relevant only to hydrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…This contrast to the quantum world, since atoms and subatomic particles have very small masses, the effect increasing of the accuracy of their positions will be accompanied by increasing uncertainty related with their velocities. It can be stated that one of fundamental principles in quantum physics is Heisenberg uncertainty since this principle reveal a fundamental aspect of the behavior of matter and energy at the quantum level (Dalimier et al, 2014), and it has important implications for our understanding of the fundamental nature of the universe. There are several applications of Heisenberg uncertainty that will discuss briefly in the following: (1) The uncertainty principle proves a limitation measurement on the precision with which certain physical quantities, such as position and momentum, also energy and time.…”
Section: 𝑃(𝑥) =mentioning
confidence: 99%
“…This contrast to the quantum world, since atoms and subatomic particles have very small masses, the effect increasing of the accuracy of their positions will be accompanied by increasing uncertainty related with their velocities. It can be stated that one of fundamental principles in quantum physics is Heisenberg uncertainty since this principle reveal a fundamental aspect of the behavior of matter and energy at the quantum level (Dalimier et al, 2014), and it has important implications for our understanding of the fundamental nature of the universe. There are several applications of Heisenberg uncertainty that will discuss briefly in the following: (1) The uncertainty principle proves a limitation measurement on the precision with which certain physical quantities, such as position and momentum, also energy and time.…”
Section: 𝑃(𝑥) =mentioning
confidence: 99%
“…The reason is the existence of an additional conserved quantity for the corresponding two-center Coulomb system with one bound electron. Recently we showed that X-dip phenomena are possible in spectral lines of helium-like ions from laser-produced plasmas [24,25]. The reason is the existence of an approximate additional conserved quantity for the corresponding two-center Coulomb system with two bound electrons [26].…”
Section: The Latest Development On X-dipsmentioning
confidence: 99%